THE DEVELOPMENT OF RESEARCH-BASED PHYSICS LEARNING MODEL WITH SCIENTIFIC APPROACH TO DEVELOP STUDENTS’ SCIENTIFIC PROCESSING SKILL (Jurnal Pendidikan IPA Indonesia, 2016)
Physics learning in SMA N 2 Padang was implemented through theory and practicum for verifying the theories. The results of the initial survey showed that the physics teachers had not yet applied the research-based learning. Supporting facilities such as physics lab and its equipment has been already available, but it has not been utilized optimally. Research-based learning is a model that can improve scientific processing skills and learning outcomes of students. The research aimed to produce a valid, practical, and effective research-based physics learning model and devices. This research was a research and development using the 4D model of Thiagarajan. The instrument of this research are interview guides, observation sheets, sheet of validation of model and learning tools, questionnaire for both teachers’ and learners’ responses, assessment sheets for scientific processing skills, and achievement test. The results showed that the developed model and the learning devices according to the assessment of experts were declared valid. Model and learning devices were practical based on the observation and the questionnaires. The application of research-based physics learning could effectively improve scientific skills and learning outcomes of students. This model is suggested to physics teachers in high school in regard with implementing research-based learning.